Dynamic Virus-Dependent Subnuclear Localization of the Capsid Protein from a Geminivirus - Wang, Liping; Tan, Huang; Wu, Mengshi; Jimenez-Gongora, Tamara; Tan, Li; Lozano-Duran, Rosa (Frontiers in Plant Science, 2017)
Viruses are intracellular parasites with a nucleic acid genome and a proteinaceous capsid. Viral capsids are formed of at least one virus-encoded capsid protein (CP), which is often multifunctional, playing additional non-structural roles during the infection cycle. In animal viruses, there are examples of differential localization of CPs associated to the progression of the infection and/or enabled by other viral proteins; these changes in the distribution of CPs may ultimately regulate the involvement of these proteins in different viral functions. In this work, we analyze the subcellular localization of a GFP- or RFP-fused CP from the plant virus Tomato yellow leaf curl virus (TYLCV; Fam. Geminiviridae) in the presence or absence of the virus upon transient expression in the host plants Nicotiana benthamiana and tomato. Our findings show that, in agreement with previous reports, when the CP is expressed alone it localizes mainly in the nucleolus and weakly in the nucleoplasm. Interestingly, the presence of the virus causes the sequential re-localization of the CP outside of the nucleolus and into discrete nuclear foci and, eventually, into an uneven distribution in the nucleoplasm. Expression of the viral replication-associated protein, Rep, is sufficient to exclude the CP from the nucleolus, but the localization of the CP in the characteristic patterns induced by the virus cannot be recapitulated by co-expression with any individual viral protein. Our results demonstrate that the subcellular distribution of the CP is a dynamic process, temporally regulated throughout the progression of the infection. The regulation of the localization of the CP is determined by the presence of other viral components or changes in the cellular environment induced by the virus, and is likely to contribute to the multifunctionality of this protein. Bearing in mind these observations, we suggest that viral proteins should be studied in the context of the infection and considering the temporal dimension in order to comprehensively understand their roles and effects in the interaction between virus and host.